PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA SD INPRES 7/83 PASEMPE KABUPATEN BONE - Nurfaizah AP; A. Endang Kusuma Amir (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2018)
The purpose of this study was to describe the application of the Teams Games Tournament (TGT) Cooperative Learning model in improving the social studies learning outcomes of fifth grade students of SD Inpres 7/83 Pasempe in Palakka District, Bone Regency. The research approach uses a descriptive qualitative approach. This type of research is classroom action research that recycles or cycles which includes planning, implementation, observation and reflection. The focus of the research is the application of cooperative learning Type Teams Games Tournament and social studies learning outcomes. The research setting was carried out at SD Inpres 7/83 Pasempe and the subject of this study were teachers and students. Data collection techniques carried out by observation, tests and documentation Data analysis techniques are qualitative which consists of three stages namely data reduction, data presentation, and conclusion drawing. The results showed that student learning outcomes had increased in each cycle. The application of the TGT cooperative learning model can improve student learning activities. In the first cycle student learning outcomes are on the medium criteria, in the second cycle are in high criteria Student learning outcomes and student learning activities have increased each cycle because there is an improvement in the learning process in each cycle. Based on the results of the study concluded that the application of cooperative learning type Teams Games Tournament can improve student learning outcomes in social studies learning in class V SD Inpres 7/83 Pasempe District Palakka Bone District.